Internet addiction and healthy life-style behaviors of high school students - Altunkürek, Şerife Zehra; Özçoban, Kardelen (Journal of Dependence, 2020)
Objective: This research was conducted for the purpose of determining internet addiction, life-style behaviors, affecting factors in high school students and relation among these. Methods: Data of the descriptive research were collected between January and March 2019. Sampling of the research was consisted of 410 students who study at a high school located in Ankara and accepted to participate into the research. Data were collected by “sociodemographic information form”, “Young’s Internet Addiction Test Short Version (YIAT-SF) and “Adolescent Life-Style Scale” questionnaire form. Results: 57.6% of students are female, 38.82% are first class students and the age average is 15.97±0.91 years. A statistically significant difference was found between students’ class, friend and family relationship state, non-course daily average internet use duration and internet use purposes and YIAT-SF total score average. Also, a statistically significant difference was found between Adolescent Life-Style Scale total score average and students’ class, friend and family relationship state, non-course daily average internet use duration and internet use purposes. A statistically negative low-level relation was found between YIAT-SF and Adolescent Life-Style Scale total and sub-dimension score average. Conclusion: Internet addiction of high school students affected the healthy life-style behavior level. It is contemplated that the study findings will contribute into school health services to be planned by identifying the requirements in this field.